1995
DOI: 10.1074/jbc.270.10.5219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Lipopolysaccharide Binding Domain in CD14 between Amino Acids 57 and 64

Abstract: CD14 is a 55-kDa glycoprotein which binds lipopolysaccharide (LPS) and enables LPS-dependent responses in a variety of cells. Recent limited proteolysis studies have implicated a region in CD14 between amino acids 57 and 64 as being involved in LPS interaction. To specifically assess the importance of this region with respect to LPS binding, we constructed a mutant sCD14 (sCD14 delta 57-64) lacking amino acids 57-64. sCD14 delta 57-64 was isolated from the serum-free conditioned medium of this cell line, and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
3
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 21 publications
9
94
3
2
Order By: Relevance
“…However, neither an epitope for 4C1 nor an LPS binding site has been identified in murine CD14 (26). In contrast, it has been demonstrated that LPS can bind to the negatively charged domain in human CD14 spanning aa 57-64 (D 57 ADPRQYA 64 ), which can be recognized by a neutralizing anti-human CD14 mAb MEM-18 (27). Moreover, it has been reported that the region at position 9 -13 (D 9 DEDF 13 ) comprising anionic amino acids is also involved in the binding of LPS to human CD14 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither an epitope for 4C1 nor an LPS binding site has been identified in murine CD14 (26). In contrast, it has been demonstrated that LPS can bind to the negatively charged domain in human CD14 spanning aa 57-64 (D 57 ADPRQYA 64 ), which can be recognized by a neutralizing anti-human CD14 mAb MEM-18 (27). Moreover, it has been reported that the region at position 9 -13 (D 9 DEDF 13 ) comprising anionic amino acids is also involved in the binding of LPS to human CD14 (45).…”
Section: Discussionmentioning
confidence: 99%
“…4C1 can block the binding of LPS to CD14 ϩ cells, whereas rmC5-3 has little effect on LPS binding (26). Ascites of anti-human CD14 mAb MEM-18, which can recognize an epitope in the region spanning aa 57-64 of human CD14 and block the binding of LPS to CD14 (27), was obtained from HyCult Biotechnology. Rabbit control IgG was prepared from nonimmunized rabbit serum by affinity chromatography using a Hitrap protein A column (Amersham Pharmacia Biotech, Little Chalfont, U.K.).…”
Section: Antibodiesmentioning
confidence: 99%
“…The LPS-CD14 complex then initiates intracellular signalling by binding to Toll-like receptor 4 (TLR4) (Aderem and Ulevitch, 2000). At least one other protein, MD-2, is associated with CD14 and TLR4 on the cell surface; together, these make up the LPS receptor (da Silva Correia and Ulevitch, 2002;Juan et al, 1995;Stelter et al, 1997;Stelter et al, 1999;Viriyakosol and Kirkland, 1995;Viriyakosol et al, 2000). The binding of C1 inhibitor to LPS (or lipid A) was inhibited by fetal bovine serum, which contains LBP, and by an LBP peptide that includes the binding site for LBP (Liu et al, 2003).…”
Section: The Interaction Of C1 Inhibitor With Gram Negative Bacterialmentioning
confidence: 99%
“…However, the mode of recognition of these structurally distinct patterns by CD14 is not clear, since structural details for CD14 in complex with any of its ligands is not available. Deletion mutagenesis experiments and epitope mapping studies with blocking antibodies and proteases have previously identified broad regions on CD14 that are crucial for binding of various microbial ligands (residues 39-44, 57-64, 81-100) and which possess overlapping sites of interaction for these ligands [11][12][13][14][15]. More recently, a highresolution X-ray crystal structure for mouse sCD14 by itself has been determined [16], in which a potential endotoxin binding pocket can be seen at the N-terminus, with the binding regions identified previously from the mutagenesis experiments clustered around this pocket.…”
mentioning
confidence: 99%